Role of the nurse in the care of a patient with mastectomized breast cancer (Research, Society and Development, 2023)
Objective: to raise the scientific evidence about the role of the nurse in front of the patient affected by mastectomized breast cancer. Methodology: the research is an integrative literature review. The databases used were Google Scholar, Latin American and Caribbean Literature in Health Sciences (LILACS), Virtual Health Library (BVS) and Scientific Electronic Library Online (SCIELO). The search for production involved the last fifteen years in order to encompass the largest number of studies. Therefore, it was carried out from 2008 to 2022. Results: the final sample consisted of seven articles, and most of them had exploratory or descriptive studies as a design option. The review reported the importance of nurses in psychosocial assistance and the use of alternative techniques in the treatment of patients who underwent mastectomy surgery, as well as highlighting the mixed emotions that women feel before, during and after mastectomy and how the nurse can help you during this period. Conclusion: mastectomy causes reactions of uncertainty, generating anguish in the face of the unknown, fear and alteration of self-image, as well as plunging women into a whirlwind of feelings and doubts. Therefore, the nurse must help to overcome such sensations, paying attention to the woman's verbal and non-verbal language, guiding her about her anxieties and being concerned with improving her quality of life.